Physical and chemical behaviour of tungsten oxide in the presence of nickel additive under hydrogen and carbon monoxide atmospheres - Salleh F.; Tahari M.N.A.; Samsuri A.; Saharuddin T.S.T.; Sulhadi S.S.; Yarmo M.A. (Elsevier Ltd, 2024)
Indexed by Scopus/ERA